2019
DOI: 10.1002/ca.23524
|View full text |Cite
|
Sign up to set email alerts
|

The ox atrioventricular conduction axis compared to human in relation to the original investigation of sunao tawara

Abstract: It was Sunao Tawara who, in 1906, established the foundations for knowledge of the arrangement of the atrioventricular conduction axis in man and other mammals. Study of the hearts of ungulates was a central part in his investigation, which assessed other species, including man. He described several subtle differences between the mammals. We have now ourselves studied the cardiac conduction tissue of the ox heart, comparing our findings with our knowledge of the arrangement in man, and providing new insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Few previous reports have described the morphometry of HB, and in most of them it has been indicated that this bundle is longer in dogs (1-1.5 mm) than in humans (0.25-0.75 mm) because the central brous body is more extensive in canines (Tawara 1906;Tawara 2000;Ho et al 1995;De Almeida et al 2020]. However, in other studies, in humans, morphometric values of HB have been reported higher than described by most of the authors and what was found in our study (1.06 x 0.23 mm), where measurements of 2.68 x 3.7 mm (Cabrera et al 2020), 11.3 x 1.8 mm (Kistin 1949) and HB width of 1-1.5 mm (Shimada and Arita 1996) are indicated, despite which based on the initial descriptions of Tawara (1906) (Kawashima and Sasaki 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Few previous reports have described the morphometry of HB, and in most of them it has been indicated that this bundle is longer in dogs (1-1.5 mm) than in humans (0.25-0.75 mm) because the central brous body is more extensive in canines (Tawara 1906;Tawara 2000;Ho et al 1995;De Almeida et al 2020]. However, in other studies, in humans, morphometric values of HB have been reported higher than described by most of the authors and what was found in our study (1.06 x 0.23 mm), where measurements of 2.68 x 3.7 mm (Cabrera et al 2020), 11.3 x 1.8 mm (Kistin 1949) and HB width of 1-1.5 mm (Shimada and Arita 1996) are indicated, despite which based on the initial descriptions of Tawara (1906) (Kawashima and Sasaki 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bovine axis takes its course due to the location of the apex of inferior pyramidal space, the substitution of the membranous septum as seen in the human heart by the main cardiac bone, and the presence of myocardial support of the non-coronary aortic valvar sinus. The availability of the methodology has permitted us to extend previous observations, including our own (Cardwell and Abramson 1931;De Almeida et al 2015, 2020bDeWitt 1909;James 1965;Kawashima and Sasaki 2011;Tawara 1906). We envisage that the methodologies used in our study will further enhance future comparative anatomical research.…”
Section: Intramyocardial Networkmentioning
confidence: 91%
“…Note the distance from the apex of the inferior pyramidal space to the left ventricular outflow tract, with the main cardiac bone interposing between them [Colour figure can be viewed at wileyonlinelibrary.com] his initial stellar investigation, Tawara (1906) had shown that, in the human heart, the atrioventricular node was positioned slightly apically relative to the nadir of non-coronary aortic valvar sinus. He also showed that, when seen from the left side, the bovine node was also positioned at the level of the nadir of noncoronary sinus, albeit slightly more basally and inferiorly (Figures 5 and 6) (De Almeida et al, 2020b).…”
Section: F I G U R Ementioning
confidence: 93%
See 2 more Smart Citations